KEMAMPUAN SPASIAL SISWA BERDASARKAN PEMAHAMAN KONSEP BIDANG DATAR DI MTs NEGERI 2 PONTIANAK - Emran Udi Raharjo; Zubaidah Zubaidah; Bistari Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
AbstractThis research aim to knowing and describe the spatial ability of students based on understanding the concept of a flat field at MTs Negeri 2 Pontianak. The research method used descriptive method with survey. The subject in this research were 36 students 9th grade of MTs Negeri 2 Pontianak which is divided into three levels that are concept understanding of high, medium, and low levels. The result of the data analysis showed that the spatial ability of students based on understanding the concept of a flat field has their respective dominance. Some have the same level of dominance and some have different levels of dominance, because the ability of each level is different. The spatial ability of students based on understanding the concept of a flat field high-level on the dominant element visualization and orientation spatial. The spatial ability of students based on understanding the concept of a flat field medium-level on the dominant element visualization and orientation spatial. The spatial abilities of students based on the two dimensional concept understanding low-level on the dominant element visualization.Keywords: Spatial Ability, Concept Understanding, Flat Field